2023
DOI: 10.3390/plants12081651
|View full text |Cite
|
Sign up to set email alerts
|

SDG26 Is Involved in Trichome Control in Arabidopsis thaliana: Affecting Phytohormones and Adjusting Accumulation of H3K27me3 on Genes Related to Trichome Growth and Development

Abstract: Plant trichomes formed by specialized epidermal cells play a role in protecting plants from biotic and abiotic stresses and can also influence the economic and ornamental value of plant products. Therefore, further studies on the molecular mechanisms of plant trichome growth and development are important for understanding trichome formation and agricultural production. SET Domain Group 26 (SDG26) is a histone lysine methyltransferase. Currently, the molecular mechanism by which SDG26 regulates the growth and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Trichomes are the first line of defense for plants in that they protect stems and leaves against pathogen or herbivore attack [ 1 , 2 , 3 ]. They also play important roles in the induction of pollination, resistance in extreme environments, protection against ultraviolet radiation and high temperatures, prevention of mechanical damage, and tolerance to heavy metals, drought, and salinity [ 4 ]. Trichomes are large, specialized epidermal cells that are distributed on various organs of a plant’s above-ground parts.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Trichomes are the first line of defense for plants in that they protect stems and leaves against pathogen or herbivore attack [ 1 , 2 , 3 ]. They also play important roles in the induction of pollination, resistance in extreme environments, protection against ultraviolet radiation and high temperatures, prevention of mechanical damage, and tolerance to heavy metals, drought, and salinity [ 4 ]. Trichomes are large, specialized epidermal cells that are distributed on various organs of a plant’s above-ground parts.…”
Section: Introductionmentioning
confidence: 99%
“…Trichomes are large, specialized epidermal cells that are distributed on various organs of a plant’s above-ground parts. They are involved in development and help to prevent excess transpiration [ 4 , 5 ]. There are two types of trichomes: non-glandular epidermal trichomes (bristles and hairs) and glandular trichomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salicylic acid (SA), gibberellins (GA), Cytokinin (CTK), and Jasmonic acid (JA), are examples of phytohormones that have been demonstrated to influence trichome initiation and morphogenesis [20,33]. Additionally, research has demonstrated that the expression of several genes, including GLABRA1 (GL1) and TRANSPARENT TESTA GLABRA1 (TTG1), is essential for the growth of trichomes [34,35]. Understanding the complex interactions between these variables can help explain how trichome formation is regulated and how it might be used in biotechnology and agriculture.…”
Section: Introductionmentioning
confidence: 99%